Biofabrication of Chitosan-Based Nanomedicines and Its Potential Use for Translational Ophthalmic Applications - Riddhi Vichare; Inyoung Garner; Ryan J. Paulson; Radouil Tzekov; Nurettin Sahiner; Siva K. Panguluri; Subhra Mohapatra; Shyam S. Mohapatra; Ramesh Ayyala; Kevin B. Sneed; Manas R. Biswal (Applied Sciences, 2020)
Drug delivery to the anterior and posterior segment of eye remains a challenge. Nanoparticle-mediated drug delivery has indicated some promise. The presented review aims to summarize recent advancements in chitosan-based nanotherapies for ocular drug delivery and the challenges encountered during the process. Significant research using chitosan, a cationic linear polymer, is being conducted for ocular drug delivery. A vast number of publications exploit the mucoadhesive properties of the polymer, which arise due to interactions between the amino acids of chitosan and the sialic acid residues in mucous. The high degree of crosslinking in chitosan nanoparticles facilitates a dramatic increase in ocular drug retention of the desired drug, which subsequently helps in ocular penetration and improving the bioavailability of the drugs. A noted decrease in the initial burst of the drug is the basis for developing sustained drug release formulation using biodegradable and biocompatible chitosan polymer. In vitro as well as in vivo studies have indicated enhancement in the uptake, accumulation, and removal of chitosan nanoparticles from the site of delivery. In summary, chitosan- or modified-chitosan-based nanoparticles are being widely tested as drug carriers for treatment of bacterial and viral infections, glaucoma, age-related macular degeneration, and diabetic retinopathy.